Numerical analysis of the impact of engineering constructions on heat loss of channel-free heat pipelines - V.Yu. Polovnikov (Инженерно-строительный журнал, 2014)
The work shows the results of mathematical modelling of thermal conditions for channel-free heating network laid in the areas of influence of engineering constructions, as well as the results of numerical analysis of heat losses in the objects under examination. The regularities of heat transfer in the system concerned and the factors influencing intensification of heat losses are revealed. The heat losses in channel-free pipes laid in the areas of engineering constructions influence have been found to decrease in the range from 1.53 to 10.79%, depending on the temperature inside any given engineering structure and geometric characteristics of the system under examination. It is demonstrated that the standard method of heat loss calculation for channel-free heating pipes overestimates values of heat loss.